Activity patterns and behavior of Myocastor coypus in a gated community in the metropolitan area of Buenos Aires (Argentina). Issue 1 (17th January 2022) - Salas, Magdalena; Hernandez-Hernandez, Julio C; Iglesias, Martín; Corriale, María J
Abstract: Anthropization processes confront local wildlife with a new set of conditions that may lead to local extinctions or allow the expansion of some species. This is what happens with the coypu ( Myocastor coypus ) in gated communities in the metropolitan area of Buenos Aires (Argentina), where its rapid population growth results in continuous conflicts with the local inhabitants. The aim of this study was to document the daily and seasonal activity patterns and behavior of the coypu in an urban landscape within their natural distribution range. To achieve this, we conducted a camera-trap survey within areas occupied by the species from February to November 2018. The coypu activity was mainly crepuscular and nocturnal with variations between seasons. We found that the seasons with the greatest activity patterns overlap were winter and autumn (84%), while the least overlap was observed between summer and winter (53%). During the active periods, time spent on foraging behavior was dominant. Time dedicated to vigilance was greater in summer than in winter. This result, alongside an increase in nocturnal activity during summer, shows that coypu in this urban landscape shift its behavior when exposed to an increasing human activity. This study brings up more ecological data of this species, which is key to find alternative control methods within gated communities to lead to a harmonic relationship between inhabitants and the species in its native distribution.